2005
DOI: 10.1523/jneurosci.3841-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Pain Upregulates Spinal Inhibition via Endogenous Neurosteroid Production

Abstract: Inhibitory synaptic transmission in the dorsal horn (DH) of the spinal cord plays an important role in the modulation of nociceptive messages because pharmacological blockade of spinal GABA A receptors leads to thermal and mechanical pain symptoms. Here, we show that during the development of thermal hyperalgesia and mechanical allodynia associated with inflammatory pain, synaptic inhibition mediated by GABA A receptors in lamina II of the DH was in fact markedly increased. This phenomenon was accompanied by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
80
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 49 publications
7
80
0
2
Order By: Relevance
“…At earlier time points (days 7 and 14), their levels remained unchanged. This pattern was consistent with previous studies in the spinal cord and the brain [15,17,39].…”
Section: Elevated Neurosteroids In the Lateral Thalamus In The Chronisupporting
confidence: 93%
See 3 more Smart Citations
“…At earlier time points (days 7 and 14), their levels remained unchanged. This pattern was consistent with previous studies in the spinal cord and the brain [15,17,39].…”
Section: Elevated Neurosteroids In the Lateral Thalamus In The Chronisupporting
confidence: 93%
“…However, most research has focused on the spinal level [15][16][17]39]. Only two studies have reported elevated neurosteroids in nociceptive supraspinal nuclei [39] and the brain [17].…”
Section: Elevated Neurosteroids In the Lateral Thalamus In The Chronimentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, we propose that inhibition of sEH reveals the activity of a physiological system that is already in place to cope with inflammatory pain. Second, Poisbeau et al (49) reported that during peripheral inflammatory pain GABA A receptormediated synaptic inhibition was enhanced in lamina II dorsal horn neurons in a manner that can be reversed with finasteride, a neurosteroid synthesis inhibitor. The inhibitory influence of GABAergic tone on ascending pain transmission and the excitability of dorsal horn neurons are well established (50).…”
Section: Discussionmentioning
confidence: 99%